Use of Psychoactive Medications and Risk of Suicide in Late Life (75+): A Total Population Study - Khedidja Hedna; Margda Waern (Adis, Springer Healthcare, 2023)
Abstract Background Psychoactive medications play an important role for the mental health and risk of suicidal behaviour in the oldest segment of the population (75+). A better understanding of psychoactive medication use is advocated to prevent suicide in this age group. Purpose We investigated the risk of suicide associated with the use of psychoactive medications in the total population aged ≥ 75 years, with and without exposure to antidepressants. Method A national population-based register study, including all Swedish residents aged ≥ 75 years between 2006 and 2014 (N = 1,413,806). A nested case-control design was used to investigate psychoactive medications associated with suicide among users and non-users of antidepressants. Risk estimates were calculated in adjusted conditional logistic regression models for the entire cohort and by gender. Results Suicide occurred in 1305 persons (907 men and 398 women). Among them, 555 (42.5%) were on an antidepressant at the time of suicide. Adjusted incidence rate ratio (aIRR) for suicide was increased in those who were on hypnotics in the total cohort (aIRR 2.05, 95% confidence interval 1.74 to 2.41), in both users and non-users of antidepressants and for both genders. Elevated suicide risk was observed in those who concomitantly used anxiolytics with antidepressants (1.51, 1.25 to 1.83). Decreased risk of suicide was observed among those who were on anti-dementia drugs, in the total cohort (0.33, 0.21 to 0.52) and in both users and non-users of antidepressants. Use of antipsychotics and mood stabilisers showed no effect on suicide risk. Conclusion Use of hypnotics and concomitant use of anxiolytics with antidepressants was associated with increased risk of late-life suicide. Our findings suggest the need for careful evaluation of the benefit-risk balance of psychoactive medications as well as their availability as a possible suicide means. Future research should consider the indication of use of the psychoactive medications and the severity of psychiatric and medical illnesses of the patients.